Technology of the Guitar - French, Richard Mark (Springer US : Imprint: Springer, 2012)
Featuring chapters on physics, structure, sound and design specifics, Technology of the Guitar also includes coverage of  historical content, composition of strings and their effects on sound quality, and important designs. Additionally, author Mark French discusses case studies of historically significant and technologically innovative instruments. This is a complete reference useful for a broad range of readers including guitar manufacturer employees, working luthiers, and interested guitar enthusiasts who do not have a science or engineering background.